Keperluan latihan berasaskan kompetensi kakitangan barisan hadapan hotel bajet, Johor Bahru - Shariff, Siti Suraya (2015)
The rapid growth of the budget hotel service these days is no longer an exceptional case. With the projected increase in this sector, front-line staffs are the first to deal with customers. Therefore, this study was undertaken to identify the training needs among front-line staff who work in budget hotels. The study was conducted on the 39 front-line staff working in 39 budget hotels in Johor Bahru. Among the aspects studied is the problem of staff performance, competencies needed for front-line staff and the necessary training provided to them. This study used qualitative and quantitative methods and qualitative research which was conducted by interviewing with three (3) important individual in the budget hotel sector, while for quantitative methods researchers have also distributed questionnaires to the respondents. The qualitative data analysis was conducted by reproducing the data and quantitative data were analyzed using SPSS program. The study found that the performance issue of front-line staff is divided into three aspects which is knowledge, skills and attitudes. There are three (3) aspects of competencies required as front-line staff which is technical, academic and personal effectiveness. This study found that front-line staffs are at a moderate level. This study also identified training needs and competency gaps found that there were any competence held by the respondent did not match with actual competencies. The study also suggests training that should be given to front-line staff in the budget hotel sector.